PENATALAKSANAAN FISIOTERAPI PADA KONDISI OSTEOARTHRITIS KNEE DEKSTRA DENGAN MODALITAS ULTRASOUND DAN TERAPI LATIHAN DI RSUD Prof. Dr. MARGONO SOEKARJO - Merri Yusdiana; Eko Budi Prasetyo (LPPM Universitas Pekalongan, 2012)
Osteoarthritis is a common rheumatic disease and causes pain and inability to perform daily activities. Osteoarthritis is caused by several factors such as: age, obesity, physical activity, sex, hormonal, and idiopathic causes damage to the cartilage resulting in reduced mobility, pain and decreased muscle strength. Handlers in this state first examined pain with VDS scale, examination of muscle strength (MMT), examination of range of motion and functional activity. The modalities used in this condition is Ultra Sound (US) and exercise therapy. From the results obtained, it can be concluded that the use of ultrasound modalities and therapeutic exercises can help reduce the problems that arise in the case of osteoarthritis.Key words: Osteoarthritis with VDS, MMT, LGS, ADL Index, ultrasound and exercise therapy.